Shopping centre marketing : value creation and customer engagement - Krowicki, Piotr; Maciejewski, Grzegorz (New York, NY : Routledge, 2024)
"There are almost 10,000 shopping centres in Europe, and in the United States there are over 100,000, many of which have entered the end-of-life phase due to growing e-retail. Therefore, the issue of how customers perceive the value of these facilities and customer engagement in the relationship with the shopping centre is becoming increasingly important. In this book, the authors evaluate the relationship between the perceived value of a shopping centre and customer engagement by identifying consumer motives, purchase behaviour and responsiveness to marketing strategies. It offers an analysis of the conceptualization and history of shopping centres and utilizes both theoretical and empirical research, presenting results from extensive studies and building a framework for value creation in retail spaces. The book will find a wide audience among scholars interested in marketing and retail management. The practical implications discussed will also provide further research opportunities and insights for astute practitioners"--
Keywords: Shopping centers; Marketing -- Management; Customer relations -- Management; Consumer satisfaction; BUSINESS & ECONOMICS / Industries / Retailing; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Marketing / Research